Evaluating a train-the-trainer approach for improving capacity for evidence-based decision making in public health. Issue 1 (June 2015) - Yarber, Laura; Brownson, Carol; Jacob, Rebekah; Baker, Elizabeth; Jones, Ellen; Baumann, Carsten; Deshpande, Anjali; Gillespie, Kathleen; Scharff, Darcell; Brownson, Ross
Abstract Background Evidence-based public health gives public health practitioners the tools they need to make choices based on the best and most current evidence. An evidence-based public health training course developed in 1997 by the Prevention Research Center in St. Louis has been taught by a transdisciplinary team multiple times with positive results. In order to scale up evidence-based practices, a train-the-trainer initiative was launched in 2010. Methods This study examines the outcomes achieved among participants of courses led by trained state-level faculty. Participants from trainee-led courses in four states (Indiana, Colorado, Nebraska, and Kansas) over three years were asked to complete an online survey. Attempts were made to contact 317 past participants. One-hundred forty-four (50.9 %) reachable participants were included in analysis. Outcomes measured include frequency of use of materials, resources, and other skills or tools from the course; reasons for not using the materials and resources; and benefits from attending the course. Survey responses were tabulated and compared using Chi-square tests. Results Among the most commonly reported benefits, 88 % of respondents agreed that they acquired knowledge about a new subject, 85 % saw applications for the knowledge to their work, and 78 % agreed the course also improved abilities to make scientifically informed decisions at work. The most commonly reported reasons for not using course content as much as intended included not having enough time to implement evidence-based approaches (42 %); other staff/peers lack training (34 %); and not enough funding for continued training (34 %). The study findings suggest that utilization of course materials and teachings remains relatively high across practitioner groups, whether they were taught by the original trainers or by state-based trainers. Conclusions The findings of this study suggest that train-the-trainer is an effective method for broadly disseminating evidence-based public health principles. Train-the-trainer is less costly than the traditional method and allows for courses to be tailored to local issues, thus making it a viable approach to dissemination and scale up of new public health practices.